Shear Transferring Mechanisms in a Composite Shallow Cellular Floor Beam with Web Openings. (February 2017) - Huo, Bing Y.; D'Mello, Cedric A.
Abstract: A new type of composite shallow floor beam has been developed to minimise the overall structural depth and provide service integration. The new composite shallow floor beam consists of an asymmetric steel section with regularly spaced web openings and a concrete slab incorporated between the top and bottom flanges. The web openings are filled with in-situ concrete when the floors are cast. The longitudinal shear force is transferred by the concrete plugs passing through the web openings, acting with or without reinforcing tie-bars. This paper presents an experimental investigation of the shear transferring mechanisms in a flexural bending test carried out on a full-scale composite shallow cellular floor beam prototype. The flexural test provided information on the slip behaviour and shear performance of the shear transferring mechanisms under a loading profile similar to uniformly distributed loading. The flexural test demonstrated significant composite action and that the flexural failure of the beam specimen was due to failure of the concrete plugs.